Sea level variations at the Latvian coastal hydrologic stations - Haritonova, Diāna (Geodesy and Cartography, 2016)
The objective of this paper is to analyse water level variations of the Baltic Sea on the Latvian coast. This is important because the Baltic Sea exhibits a number of remarkable phenomena. One of them is the sea level variations due to winds, complicated by the shape of the gulfs and islands. Under this influence the range of the sea level variations can reach 3 m on the coasts of gulfs. However, the tidal variations of the Baltic Sea range in the order of centimetres only. In the frame of this study, using hourly time series of the sea level records from 7 Latvian coastal hydrologic stations and employing spectral analysis, it has become feasible to identify diurnal and semi-diurnal tide existence both in the Gulf of Riga and in the Baltic Sea at the Latvian coast. Totally 4 main tidal constituents (O1, K1, M2, S2) have been identified. Additionally, nontidal frequency of 5 cycles per day has been detected in the sea level time series of the stations located in the Gulf of Riga.